Conservative treatment of pediatric thoracic and lumbar spinal fractures: outcomes in the sagittal plane. Issue 1 (January 2017) - Angelliaume, Audrey; Simon, Anne-Laure; Boissière, Louis; Bouty, Aurore; Sales de Gauzy, Jérôme; Vital, Jean-Marc; Gille, Olivier; Tournier, Clément; Aunoble, Stéphane; Pontailler, Jean-Roger; Lefèvre, Yan
Abstract : To assess sagittal plane spinopelvic balance and functional outcomes in a pediatric cohort of patients with a thoracic and/or a lumbar fracture treated conservatively. A multicentric study retrospectively reviewed radiological and functional outcomes (mean follow-up 49 months) of 48 patients (mean age 12 years) with thoracic and/or lumbar spinal fractures that occurred between 1996 and 2014. Demographic data and radiological spinopelvic parameters were analyzed. Functional outcome was evaluated by a telephone interview. First, a comparison between the initial and the last follow-up full-spine radiographs was performed for the assessment of bone remodeling and sagittal plane balance. Then, patients were classified into two groups (group 1: Risser⩽2 and group 2, Risser>2) to assess the influence of skeletal maturity on the restoration of a correct sagittal balance. A total of 62% of the patients were at skeletal maturity at the final follow-up (Risser 4 and 5). Patients with a Risser grade of 2 or less had a higher remodeling potential. The mean residual local kyphosis in thoracic and lumbar fractures was, respectively, 8.2° and 8.7°. The mean thoracic global kyphosis remains stable at the last follow-up, in contrast to lumbar lordosis, which increased significantly. Sagittal plane global measurements on the basis of the C7-plumbline remained unchanged at the last follow-up. There was no change in the pelvic parameters, except for the sacral slope in the group 1 for patients with a lumbar fracture. The current study confirms a greater correction in younger patients (Risser⩽2) in spinal fractures and reported that thoracic fractures have a higher remodeling potential than lumbar fracture. A local kyphosis of almost 10° remained at the last follow-up. However, no deterioration in the sagittal plane balance was found. This suggests compensatory mechanisms in adjacent structures for children and adolescents and excludes the only hypothesis of bone remodeling.